Development of simulant samples of nuclear-magnetic relaxation characteristics of sunflower lecithins - O. S. Agafonov; E. P. Viktorova; S. M. Prudnikov; T. A. Shahray; E. V. Velikanova (Новые технологии)
The article presents the results of the investigation of NMR characteristics of protons contained in sunflower lecithins. The basic requirements for creating NMR simulant samples of proton characteristics contained in sunflower lecithins are formulated. The results of the investigation of NMR characteristics of organosilicon fluids of various brands are presented in order to select the most effective simulant samples. The composition of simulant samples of NMR proton characteristics contained in sunflower lecithins is developed, the application of which will significantly simplify the process of calibration and verification of NMR analyzers.